Effect of temperature on the pulse‐echo performance of ultrasonic transducers fabricated with PVDF film. Issue 3 (1st May 2019) - Kelley, Thomas
Abstract : Empirical data is presented on the pulse‐echo performance of poly‐vinylidenefluoride (PVDF) ultrasound transducers monitored in‐situ at temperatures in the range 50–130°C. Measurements were performed over a 5 h period beginning at the sensors' initial exposure to temperature. A reduction in pulse‐echo amplitude was observed at all temperatures in the range and was found to be proportional to temperature increase. Four different thicknesses of PVDF film were used for the trials and small differences in behaviour were observed between sensors constructed using each thickness. On average, the overall loss was found to increase linearly with temperature from a 16% drop in pk–pk pulse‐echo voltage observed at 60°C to a 95% drop in performance at 120°C after 5 h. Rates of signal loss were found to follow a logarithmic decay, particularly at temperatures above 70°C where significant reductions were observed in the initial seconds/minutes following exposure to temperature.